Bacterial RNA:DNA hybrids are activators of the NLRP3 inflammasome - Kailasan Vanaja, Sivapriya (National Academy of Sciences, 2014)
Enterohemorrhagic Escherichia coli (EHEC) is an extracellular pathogen that causes hemorrhagic colitis and hemolytic uremic syndrome. The proinflammatory cytokine, interleukin-1β, has been linked to hemolytic uremic syndrome. Here we identify the nucleotide-binding domain and leucine rich repeat containing family, pyrin domain containing 3 (NLRP3) inflammasome as an essential mediator of EHEC-induced IL-1β. Whereas EHEC-specific virulence factors were dispensable for NLRP3 activation, bacterial nucleic acids such as RNA:DNA hybrids and RNA gained cytosolic access and mediated inflammasome-dependent responses. Consistent with a direct role for RNA:DNA hybrids in inflammasome activation, delivery of synthetic EHEC RNA:DNA hybrids into the cytosol triggered NLRP3-dependent responses, and introduction of RNase H, which degrades such hybrids, into infected cells specifically inhibited inflammasome activation. Notably, an E. coli rnhA mutant, which is incapable of producing RNase H and thus harbors increased levels of RNA:DNA hybrid, induced elevated levels of NLRP3-dependent caspase-1 activation and IL-1β maturation. Collectively, these findings identify RNA:DNA hybrids of bacterial origin as a unique microbial trigger of the NLRP3 inflammasome.